(untitled) (Metallurgy and Foundry Engineering, 2017)
This paper analyzes the problem of susceptibility to hydrogen-assisted cracking (fracture behavior) of zinc-coated screws made of 30MnB4 steel. Two samples (screws) were compared after proper and improper heat treatment affecting hydrogen solubility during the further galvanic process and resulting in different fracture modes. Both samples were loaded to failure by torsion. The fracture surface and microstructure of the samples were examined using scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDS).